2017
DOI: 10.1038/nnano.2017.175
|View full text |Cite
|
Sign up to set email alerts
|

Protein recognition by a pattern-generating fluorescent molecular probe

Abstract: Fluorescent molecular probes have become valuable tools in protein research; however, the current methods for using these probes are less suitable for analysing specific populations of proteins in their native environment. In this study, we address this gap by developing a unimolecular fluorescent probe that combines the properties of small-molecule-based probes and cross-reactive sensor arrays (the so-called chemical 'noses/tongues'). On the one hand, the probe can detect different proteins by generating uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
95
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 47 publications
0
95
0
1
Order By: Relevance
“…Figure 1 shows the design and operating principles of a synthetic receptor system that fulfills these requirements. This design borrows principles from our previous studies in which we demonstrated the possibility of generating ODN-small-molecule conjugates that can non-covalently bind to several different proteins 21,22 . We hypothesized that if one of the protein targets for such synthetic protein binders would be located on the cell surface, their regulatory effect 21 could be extended from the protein level to the cellular level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the design and operating principles of a synthetic receptor system that fulfills these requirements. This design borrows principles from our previous studies in which we demonstrated the possibility of generating ODN-small-molecule conjugates that can non-covalently bind to several different proteins 21,22 . We hypothesized that if one of the protein targets for such synthetic protein binders would be located on the cell surface, their regulatory effect 21 could be extended from the protein level to the cellular level.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, considerable attention has been devoted to developing protein binders based on oligodeoxynucleotide (ODN)-small-molecule conjugates [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] that, similar to CSPs, can respond to external stimuli and undergo dynamic structural changes that enable them to reversibly interact with proteins and regulate their functions [11][12][13][14][15][16][17][18][19][20][21] . We have recently developed protein binders based on ODN-small-molecule conjugates [21][22][23] and have shown that such binders can be designed to reversibly interact with different proteins 21,22 and even mediate unnatural protein-protein communication processes 21 . Parallel to these efforts, much progress has been made in the ability to modify cell surfaces with synthetic agents that bear unique functionalities [28][29][30][31] .…”
mentioning
confidence: 99%
“…Herein, we propose to also analyze 2PA‐induced CO release as a new form of molecular logic gates. The optically activated, cancer‐targeted CORMs presented in this work display excellent properties as molecular logic devices since they can process concomitantly electromagnetic, chemical, and environmental information …”
Section: Methodsmentioning
confidence: 99%
“…[27] Herein, we propose to also analyze 2PA-induced CO release as an ew form of molecular logic gates.T he optically activated, cancer-targeted CORMs presented in this work display excellent properties as molecular logic devices since they can process concomitantly electromagnetic, chemical, and environmental information. [28][29][30] Herein, photoCORMsc ompounds 1-2 (Scheme1)c ombine a [Mn I (CO) 3 ]C O-rich fragment with ap otentially emissive dipicolylamine-1,8-naphthalimide ligand,w hile 2 also integrates a biotin tether.T he turn-on fluorescent chromophore 1,8-naphthalimide has al arge2 PA cross-section [31][32][33][34] and can be excited between l exc = 600-950 nm. [35][36][37][38] Biotin is required to sustain the natural growth of eukaryotic cells.…”
mentioning
confidence: 99%
“…Kürzlich berichteten Margulies et al. über eine elegante, mehrteilige Fluoreszenzsonde mit drei fluoreszierenden proteinbindenden Einheiten: einer DNA‐Aptamer‐Haarnadel und zwei zusätzlichen Proteinerkennungsstellen auf Basis niedermolekularer Verbindungen (Abbildung ) . Ausgewählt wurden die Proteinerkennungsstellen anhand bekannter, nicht‐spezifischer bindender Wechselwirkungen mit krankheitsassoziierten Proteinfamilien, wie Glutathion‐S‐Transferasen (GSTs), Matrix‐Metalloproteasen (MMPs) und thrombozytären Wachstumsfaktoren (PDGFs).…”
Section: Array‐basierte Sensoren Für Biomedizinische Anwendungenunclassified